Leveraging smartphone mobility data to understand HIV risk among rural South African young adults: feasibility study - Mathenjwa, Thulile; Okango, Elphas Luchemo; Tram, Khai Hoan; Inghels, Maxime; Cuadros, Diego; Kim, Hae-Young; Walsh, Fiona; Bärnighausen, Till; Dobra, Adrian; Tanser, Frank (JMIR mhealth and uhealth, 2025)
Background: Smartphones provide a precise method to study human mobility at an unprecedented scale, allowing researchers to explore the links between mobility, HIV risk and treatment outcomes. However, leveraging smartphone technology to study HIV risk in rural settings presents unique challenges and opportunities. Objective: This study assessed the feasibility of using smartphone GPS technology to collect mobility data from young adults in rural KwaZulu Natal, South Africa. We also present key lessons learned during the study. Methods: The study was conducted in two phases (June 2021 - May 2023) with males and females aged 20-30 years old. In phase I, participants received smartphones with a customized study app (Avicenna research software). In phase II, they used their personal smartphones and installed the study app. The app used Android location services to record the smartphone location every 30-minutes and send it to a secure study server hourly. Participants were followed-up for six months (26 weeks). If location data were missing for 48-72 hours, participants were contacted for troubleshooting. Engagement strategies, including reverse billing and gamification (wheel of fortune), were implemented to address internet connection barriers and aid data collection. Results: A total of 207 participants were enrolled (Phase I - 163, phase II - 44) with 204 providing mobility data. Participants recorded 27.6 million location points with a median number of 74,865 [IQR 28,471 - 186,578] per participant. The mean weekly location points recorded was 95.3 out of 336 possible half hour intervals (28.4%). Phase II saw more stable data collection in the latter half of the study, due to increased user engagement with the app. Challenges included phone-related issues (screen malfunctions, lost/broken phone), app terminations and limited internet connectivity. Reverse billing and gamification strategies improved location data collection through increased user engagement. Conclusions: While only 28.4% of expected weekly location data were collected, this study offers insights into engagement strategies that can be employed to enhance location data collection in rural settings. Continuous troubleshooting identified challenges and informed solutions to data collection gaps. Reverse billing system and gamification resulted in significant increases in location data received, underscoring the potential for adaptation in similar studies.
Gesehen am 02.02.2026